Spinal muscular atrophy with severe scoliosis: a case report - Dikahayu Alifia Anugrah; Sunartini Sunartini; Mohammad Juffrie (Indonesian Pediatric Society, 2023)
Spinal muscular atrophy (SMA) is an autosomal recessive neurodegenerative disease that causes general weakness, muscle atrophy, and poor muscle movement. This condition is due to a homozygous disruption of the survival motor neuron (SMN) 1 survival gene due to deletion, conversion, or mutation.1